Exploring Milk Consumption Trends and Cow Milk Health Benefits Awareness: A Consumer Analysis in Anand and Vidyanagar Cities - , Anant Chaudhari, A.K. Makwana, M.D. Gurjar, K.C. Kamani, M.C. Prajapati (Archives of Current Research International, 2024)
This study investigates the consumption patterns and consumer awareness of cow milk in Anand and Vidyanagar cities. India, as the largest milk producer globally, relies heavily on cow milk, which plays a crucial role in the national economy and rural livelihoods. Unlike other milk options such as goat's milk, cow milk is predominantly consumed due to its widespread availability, affordability, and established preference among Indian households. This research also aims to debunk common myths surrounding cow milk and explore consumer perceptions of special cow milk variants. Through a survey of 200 respondents, the study reveals demographic characteristics, milk consumption habits, and awareness levels regarding cow milk's health benefits. The results show a high prevalence of milk consumption (99%) with a preference for packed milk (67%) and daily consumption (78.5%). However, consumer awareness about cow milk's nutritional content and health benefits was relatively low. The study employs descriptive statistics, Chi-square tests, and the Karl Pearson Correlation Coefficient to analyze the data, finding no significant association between income and cow milk consumption and education level and cow milk consumption, but a positive correlation between age and milk consumption. The findings underscore the need for increased consumer education on the nutritional benefits of cow milk to enhance informed consumption choices. These insights can guide policymakers and industry stakeholders in designing effective educational campaigns and interventions to promote cow milk, ultimately supporting healthier dietary practices and boosting the dairy sector's growth.